Kajian Pondasi Sumuran pada Jembatan Bo'u Lahomi Kabupaten Nias Barat. - Rizky Franchitika; Kartika Indah Sari; Yustinus Y.P Gulo (Universitas Harapan Medan, 2022)
The Bo'u Lahomi-West Nias Bridge is a bridge that spans 11.80 m. The sub-structure of the bridge consists of abutments and foundations. This evaluation was conducted to determine the bearing capacity of the well foundation and the safety factor against the working load along with an evaluation of the analysis of the amount of foundation reinforcement and pile cap. The safety factor for the bearing capacity of the well foundation is determined based on the comparison of the bearing capacity value of the well foundation > with the maximum load value that works on the foundation, while the safe factor for pile cap reinforcement and the well foundation is determined based on the strength value of the column > with the maximum load value received. In addition to field data, this analysis requires testing of soil parameters in the laboratory. The meters tested were specific gravity (Gs), filter analysis of moisture content, density, direct shear strength of the soil in the field. Based on the results of the analysis of the bearing capacity of the well foundation, it was found that the value of the bearing capacity of the pile foundation group was 2510,78 tons and the maximum load acting on the foundation was 1550,40 tons. 15 13, and shear reinforcement in the direction of X 10 – 140 and Y 10 – 100 and analysis of reinforcement on the well foundation obtained 35 D 19-250 principal reinforcement and spiral reinforcement 12 – 50 with a column strength of 7654.153 Ton > Pu = 1550.40 Tons, thus the bearing capacity of the well foundation on the bo'u bridge meets the requirements and is safe against the load received and the column cross-sectional design meets the requirements so that the size of the piles and reinforcement can be used.